Orthotic bicycle shoe insoles show no effects on leg muscle activation patterns or performance in recreational cyclists. (2nd September 2017) - Meyers, A.C.; Caldwell, E.C.; Hirsch, J.; Jacobs, K.A.; Pohlig, R.T.; Signorile, J.F.
Abstract : This study tested the hypothesis that an orthotic insole in cycling shoes would stabilize pedalling mechanics, reduce or alter activity of the quadriceps and hamstring muscles, and reduce physiological work while cycling. Nine cyclists were evaluated during four VO2max tests, using four different insole conditions (flat (no insole), low, medium, and high arch supports) in a random order. Wireless electromyography (EMG) was used to measure muscle activity, and telemetry-based gas analysis and power output to determine cycling efficiency. The non-flat insole that resulted in the lowest level of lateral knee movement was identified as 'best fit'. General linear mixed models were run two ways, with the most effective insole for the dominant leg and non-dominant leg identified as the overall 'best fit' insoles. There was an interaction for the dominant leg hamstrings EMG ratio among insoles and pedal float type ( p = .007). Heart rate at anaerobic threshold was reduced by best fit insoles for the dominant leg ( p = .014) and non-dominant leg ( p = .017); this may be the result of hydration status or existing fatigue. The results indicate that arch support alone does not have an effect on mediolateral EMG ratios of the quadriceps or hamstrings, or performance. Further investigation of insole effects on muscle activation patterns is warranted.